Investigation on the role of biallelic variants in VEGF‐C found in a patient affected by Milroy‐like lymphedema. Issue 9 (26th June 2020) - Mukenge, Sylvain; Jha, Sawan K.; Catena, Marco; Manara, Elena; Leppänen, Veli‐Matti; Lenti, Elisa; Negrini, Daniela; Bertelli, Matteo; Brendolan, Andrea; Jeltsch, Michael; Aldrighetti, Luca
Abstract: Background: Milroy‐like disease is the diagnostic definition used for patients with phenotypes that resemble classic Milroy disease (MD) but are negative to genetic testing for FLT4 . In this study, we aimed at performing a genetic characterization and biochemical analysis of VEGF‐C variations found in a female proband born with congenital edema consistent with Milroy‐like disease. Methods: The proband underwent next‐generation sequencing‐based genetic testing for a panel of genes associated with known forms of hereditary lymphedema. Segregation analysis was performed on family members by direct sequencing. In vitro studies were performed to evaluate the role of a novel identified variant. Results: Two VEGF‐C variations were found in the proband, a novel p.(Ser65Arg) and a pathogenic c.148‐3_148‐2delCA, of paternal and maternal origin, respectively. Functional characterization of the p.(Ser65Arg) variation in vitro showed alterations in VEGF‐C processing. Conclusions: Our findings reveal an interesting case in which biallelic variants in VEGF‐C are found in a patient with Milroy‐like lymphedema. These data expand our understanding of the etiology of congenital Milroy‐like lymphedema. Abstract : A genetic and biochemical analysis of VEGF‐C variations were performed on a female proband affected by primary lymphedema of the right lower limb and on her entire family. Biallelic variants of VEGF‐C variations were found in the proband: a novel p.(Ser65Arg) and a pathogenic c.148‐3_148‐2del, of paternal and maternal origin, respectively. Clinical examination of the family by lymphoscintigraphy as well as biochemical analysis show that both variants are required to the development of the proband Milroy‐like lymphedema.